The Effect of TikTok Exposure on Attitudes, Subjective Norms, and Intentions to Promote Pro-Environmental Behavior among Universitas Padjadjaran Students - Arjani, Naura; Kunto Adi Wibowo; Detta Rahmawan; Ikhsan Fuady (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
Climate change necessitates behavioral transformation among Generation Z, who are heavily influenced by TikTok. This study analyzes the impact of TikTok exposure on pro-environmental behavior among Universitas Padjadjaran students using the Theory of Planned Behavior. Data from 310 respondents were processed using SEM-PLS. Results indicate that TikTok exposure significantly is significantly associated with attitudes and subjective norms, driving environmental intentions and actions. A critical finding reveals that attitude (T-Stat 10.761) serves as a stronger mediator than subjective norms (T-Stat 6.943), suggesting that personal conviction outweighs social pressure. The model shows strong predictive power, with behavioral intention demonstrating a strong association with pro-environmental behavior (T-Stat 101.724). In conclusion, TikTok effectively mobilizes environmental action by internalizing personal values rather than mere social conformity.